CHEMICAL DELIGNIFICATION OF MALANG ARABICA COFFEE HUSK WASTE FOR ALTERNATIVE ENERGY - Anggorowati, Dwi Anna; Setyawati, Harimbi; Handaratri, Anitarakhmi; Dewi, Rini Kartika; Surbakti, Sriliani (Journal of Sustainable Technology and Applied Science (JSTAS), 2025)
Malang Regency is an area that has the potential to be the largest coffee producer in Indonesia. The coffee processing in Malang Regency will yield approximately 65% coffee beans and 35% coffee husk waste, resulting in an estimated production of about 3,235 tons of coffee husk waste from a total coffee productivity of 9,245 tons. The coffee husk, a by-product of coffee processing, is a waste that has not been utilized to its full potential. Generally, people only use it for fodder and compost. The coffee husk waste contains a lignin content of 29%, hemicellulose at 24%, and the highest cellulose at 33%. Adequate cellulose content of the material for the manufacture of bioethanol is more than 30%; from the composition of Arabica coffee husk, the cellulose content is more than 30%. So it can be used as an alternative fuel, like bioethanol. This research aimed to reduce the lignin content and increase the cellulose content in coffee husk waste through chemical treatment with NaOH. The research stages involved placing 5 grams of coffee husk powder, sized at 80 mesh, into a glass beaker. Next, 50 ml of NaOH solution with concentrations of 5.0%, 5.5%, 6.0%, 6.5%, and 7.0% (v/v) was added. The sample was put in an autoclave at 121°C for 15, 30, 45, and 60 minutes. The best time was 30 minutes with an NaOH concentration of 7%, with the highest cellulose content obtained; it was 55%.